Global pentecostalism : encounters with other religious traditions - Westerlund, David (London : I.B. Tauris, 2009)
"Pentecostalism is a movement within Christianity placing special emphasis on a believer's personal encounter with God through the Holy Spirit. It is arguably the world's fastest-growing form of religion. While exact figures are uncertain, there may now be as many as 500 million Pentecostals. Closely related to other forms of 'born-again' Christianity (Evangelical and Charismatic), Pentecostalism has been described as a religion 'made to travel'. From the outset it has been a strong missionary movement, and has been oriented towards recruitment and expansion. Research into this important form of Christianity has become more popular of late, but the movement's remarkably fast spread is still not well understood. In particular, its constant worldwide encounters with other religions and beliefs, as well as with different forms of Christianity, have seldom been explored at length.This rich and varied book remedies that neglect. Although its adherents supposedly preach a universal message, in practice Pentecostalism's global spread has resulted in increasing diversification. The volume investigates the consequences of that spread, and of the accommodations Pentecostal missionaries have to make when faced by pluralism and the challenges posed by ecumenism. Ranging across every major continent, the contributors to the volume make a significant contribution towards a fuller and more complete understanding of this remarkable world faith.Pentecostalism is topical, fast-expanding, newsworthy and exotic. This is the definitive collection by international experts on the movement. It is the first book to address Pentecostalism's fascinating relationship with other faiths and beliefs."--Bloomsbury Publishing.
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Also issued in print.
Electronic reproduction.
Keywords: Pentecostalism; Pentecostalism -- History; Christianity